Medial Condyle Fracture of the Humerus Following an Arm-Wrestling Injury in an Adolescent: A Rare Kilfoyle Type II Injury with Transient Ulnar Neuropathy Managed by Open Reduction and Pinning - I Gede Mandra Adnyana; I Made Artana (HM Publisher, 2026)
Fractures of the medial condyle of the humerus are uncommon injuries in the pediatric and adolescent population, accounting for fewer than two percent of elbow fractures, yet they are clinically important because the fracture line crosses both the articular surface and the distal humeral physis. Delayed or inadequate treatment may lead to nonunion, growth arrest, cubitus varus or valgus deformity, and elbow instability. We report a 15-year-old male who presented with one month of persistent left elbow pain after an arm-wrestling contest during which the elbow shifted and he fell onto the affected arm. He described intermittent paresthesia of the ring and little fingers and morning stiffness. Examination revealed medial elbow swelling, tenderness over the medial condyle, painfully limited motion, and paresthesia in the ulnar nerve distribution. Plain radiographs confirmed a left medial condyle fracture classified as Kilfoyle type II. Because of the intra-articular nature of the injury and the risk of displacement, open reduction and internal fixation with Kirschner-wire pinning was performed, followed by intravenous fluid support, ceftriaxone for prophylaxis, and intravenous paracetamol for analgesia. One week postoperatively the patient showed marked improvement, with resolution of stiffness, reduced pain, recovered range of motion, and improvement of the ulnar nerve symptoms, and no complications were observed. This report highlights arm wrestling as a rare mechanism of adolescent medial condyle fracture, its association with transient ulnar neuropathy, and the favorable early outcome achievable with prompt anatomical fixation and structured postoperative care.